Does fund managers' timing ability depend on market conditions? Evidence from Turkish variable funds. (17th September 2021) - Yalcin, Hale; Dube, Sema
We examine market timing by Turkish variable-fund managers during 2011-2016 within a panel data framework, using interaction variables to control for market conditions. We find strong evidence for market-timing ability, which increases with country openness, global emerging-market portfolio returns, economic growth and, to a smaller extent, derivative market size; and decreases with technological advancement. We also find no evidence for security selection ability. Our results suggest that market timing ability depends on market conditions and it may be important to control for such conditions in studies that seek to determine managerial performance.